A Rasch Analysis of The Indonesian Version of Proactive Personality Scale - Prihatsanti, Unika; Prabowo, Dito Aryo; Prasetyo, Anggun Resdasari; Dewi, Kartika Sari (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2026)
Proactive personality reflects an individual’s tendency to initiate change and influence the environment, particularly in organizational contexts. This study aimed to examine the psychometric properties of the Indonesian version of the Proactive Personality Scale (PPS) using Rasch measurement modeling. A cross-sectional survey design was employed involving 307 employees from various organizations in Indonesia (40.4% male, 59.6% female; Mage = 32.46, SD = 8.38), recruited through convenience sampling. The instrument was translated and culturally adapted in accordance with International Test Commission (ITC) guidelines. Data were analyzed using the Rasch Rating Scale Model with Winsteps, applying Joint Maximum Likelihood Estimation to evaluate dimensionality, item fit, reliability and rating scale functioning. The Rasch model explained 44.1% of the variance, supporting the unidimensional assumption. The results suggest adequate person separation and stable item calibration and indicate good internal consistency (Cronbach’s α = 0.81), acceptable person reliability (0.77), also excellent item reliability (0.98), However, rating scale analysis revealed suboptimal functioning in lower response categories, indicating that collapsing categories may improve measurement precision. Overall, the Indonesian PPS demonstrates acceptable psychometric properties for research and organizational assessment purposes. Nevertheless, refinement of the response format and further validation using more diverse samples are recommended to enhance measurement precision and generalizability.